Hypotensive efficacy and cerebroprotective action of beta blocker metoprolol - N. L. Afanasyeva; V. F. Mordovin; N. Yu. Efimova; G. V. Semke; I. Yu. Efimova (Российский кардиологический журнал)
The aim of the study was to investigate hypotensive and cerebroprotective activity ofmetoprolol inpatients with essential arterial hypertension (EAR). In all participants, 24-hour blood pressure (BP) monitoring, cerebral perfusion scintigraphy, and cognitive function assessment were performed at baseline and after 6 weeks of treatment. After 6 weeks of therapy, according to 24-hour BP monitoring results, systolic and diastolic BP significantly declined. Cerebral blood flow substantially improved in parietal, frontal, and temporal areas. Cognitive function (memory, attention, thinking) also improved. Metoprolol optimally decreased BP and demonstrated cerebroprotective efficacy.